(untitled) - Boyd, Claude E. (Auburn, Alabama, 2014)
Efficient aquaculture production depends upon maintaining acceptable water quality conditions in culture units. This handbook discusses background information from chemistry, physics, biology, and engineering necessary for understanding the principles of water quality management in aquaculture. It also provides practical information about the approaches and treatments that can be used to enhance water quality in aquaculture systems. It is an excellent resource for aquaculture scientists, students, and producers.
Chuyên đề tổng hợp kiến thức chuyên ngành,Khoa học môi trường nước,Quản lý chất lượng nước trong nuôi  trồng thủy sản
Keywords: Chất lượng nước,Aquaculture,Water quality